Selective exposures in orthopaedic surgery the foot - Baumhauer, Judith F.; Digiovanni, Benedict F.; Flemister Jr. , Adolph S.; American Academy of Orthopaedic Surgeons (Rosemont, Ill. : American Academy of Orthopaedic Surgeons, 2003)
Orthpaedic surgeons use live patient surgeries and cadaveric dissections to highlight risks and potential pitfalls for each exposure. Also includes self-assessment questions, and references that include abstracts and articles by top names in orthopaedic foot surgery
Title from title screen
Approved for up to 3 hr. of AMA PRA category 1 CME credit
'Product np. 02547'--Container
Windows system requirements: Pentium class chip; Windows 98, ME, 2000, XP; Quicktime 5.0 (included); DirectX version 6.0 or later; Adobe Acrobat 5.05 or later (included); CD-ROM drive; sd. card; speakers
Macintosh system requirements: PowerPC Macintosh; MacOS 9 or OSX; color display (800x600--16 bit); CD-ROM drive; Quicktime 5.0; Macintosh audio system
Keywords: Foot -- surgery; Orthopedic Procedures -- methods